Parent Artery Occlusion in Large, Giant, or Fusiform Aneurysms of the Carotid Siphon: Clinical and Imaging Results - Labeyrie, M.-A.; Lenck, S.; Bresson, D.; Desilles, J.-P.; Bisdorff, A.; Saint-Maurice, J.-P.; Houdart, E. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Parent artery occlusion has long been considered the reference treatment for large/giant or fusiform aneurysms of the carotid siphon. However, meager recent data exist on this technique, which tends to be replaced by stent-assisted reconstructive techniques. In our department since 2004, we have assessed the safety, efficacy, and complication risk factors of parent artery occlusion by using coils for trapping these aneurysms. MATERIALS AND METHODS: We determined retrospectively the complication rate, factors associated with the occurrence of an ischemic event, changes in symptoms of mass effect, evolution of the aneurysmal size, and the growth of an additional aneurysm after treatment. RESULTS: Fifty-six consecutive patients were included, with a median age of 54 years (range, 25–85 years; 92% women), 48% with giant aneurysms and 75% with infraclinoid aneurysms. There was a permanent morbidity rate of 5% exclusively due to ischemia, a zero mortality rate, an aneurysmal retraction rate of 91%, and an improvement rate for pain of 98% and for cranial nerve palsy of 72%, with a median follow-up of >3 years. Para-/supraclinoid topography of the aneurysm (P = .043) and the presence of cardiovascular risk factors (P = .024) were associated with an excessive risk of an ischemic event, whereas the presence of a mural thrombus had a protective role (P = .033). CONCLUSIONS: In this study, parent artery occlusion by using coils to treat large/giant or fusiform aneurysms of the carotid siphon was safe and effective, especially for giant infraclinoid aneurysms. According to recent meta-analyses, these results suggest that the validation of stent-assisted reconstructive treatments for these aneurysms requires controlled studies with parent occlusion artery. BOTballoon occlusion testIEischemic eventPAOparent artery occlusionQ1–Q3interquartile range